Effectiveness of sublingual immunotherapy with house dust mite drops in asthmatic children at different ages - Ai, Tao; Zhang, Peilin; Luo, Ronghua; Fan, Yinghong; Xia, Wanmin; Wang, Li (Frontiers in Pediatrics, 2023)
Background: Respiratory allergies in children, such as asthma and rhinitis, are becoming more and more common every year. Recent studies found that pediatric asthma patients receiving regular medication and specific immunotherapy (SIT) had improved therapeutic outcomes in a wide age range. However, there are few studies that have examined the effectiveness of SIT treatment in children with allergic asthma at different ages in terms of the degree of asthma control, improvements in lung function, and changes in exhaled nitric oxide (FeNO). Method: 200 asthmatic pediatric patients who had been receiving regular treatment for at least a year were split into observation and control groups depended on whether sublingual immunotherapy (SLIT) were added on the basis of conventional treatment medicines. Children were divided by an age cut-off of 6 years old in these two groups were compared before and after therapy based on the exhaled nitric oxide levels (FeNO), pulmonary function, visual analog scale (VAS), medication scores, daytime and nighttime asthma symptom ratings, and rhinitis symptom scores. Results: All other indices did not demonstrate significant differences prior to treatment, with the exception of FVC, FEV1 and FEF25 in the comparison between older children (6-16 years old) in observation group and control group. The FEF75, FEF50, FEF25, and MMEF75/MMEF25 indices in children under the age of six in the observation group after therapy were significantly greater than those in the control group, whereas other parameters did not demonstrate statistically significant changes. Children older than 6 in observation group had higher ACT, FEF75, FEF50, MMEF72/MMEF25, and FeNO scores than the control group after treatment and these differences were statistically significant, while other indexes did not show significant differences. However, in observation group, all indexes did not show significant differences between pediatric patients in pre-school age and school age after one-year SLIT. Conclusion: Children with asthma of all ages can considerably benefit from sublingual immunotherapy. Specifically, younger patients showed greater tendence on small airway resistant improvement, whereas school-age children with asthma significantly improved their small airway resistance as well as their asthma control and inflammation alleviation.